2020
DOI: 10.1039/d0sc03736b
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylative ether dissection by iridium pincer complexes

Abstract: A unique chain-rupturing transformation that converts an ether functionality into two hydrocarbyl units and carbon monoxide is reported, mediated by iridium(I) complexes supported by aminophenylphosphinite (NCOP) pincer ligands. The decarbonylation,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…After complexation, a large amount of [Ir(ppy) 2 (di(2-pyridyl)ketone)] + was isolated in the reaction medium as side product. Despite we are not able to provide a mechanistic interpretation for such experimental evidence, actually the cleavage of the C–O ether bond by pincer iridium complexes has been previously reported in similar reaction conditions [ 34 , 35 ]. On the contrary, the ligand A4 reacts with [Ir(ppy) 2 Cl] 2 giving the stable corresponding complex [Ir(ppy) 2 ( A4 )] + .…”
Section: Resultsmentioning
confidence: 66%
“…After complexation, a large amount of [Ir(ppy) 2 (di(2-pyridyl)ketone)] + was isolated in the reaction medium as side product. Despite we are not able to provide a mechanistic interpretation for such experimental evidence, actually the cleavage of the C–O ether bond by pincer iridium complexes has been previously reported in similar reaction conditions [ 34 , 35 ]. On the contrary, the ligand A4 reacts with [Ir(ppy) 2 Cl] 2 giving the stable corresponding complex [Ir(ppy) 2 ( A4 )] + .…”
Section: Resultsmentioning
confidence: 66%
“…The three ligands were prepared according to recently reported procedures. 17,18 The methoxy group in the backbone was selected to prevent unwanted metalation at the site ortho to the phosphinite (para to the amine donor). 11,19 Refluxing Pd(COD)Cl2 with the ligand produced square planar palladium(II) chloride complexes with tridentate NCOP pincer coordination.…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies investigating the activation of MeOAc by previously reported (NCOP)­Ir­(CO) complexes did not show promising reactivity, despite the ability of these carbonyl complexes to carry out the individual steps and overall catalytic reaction of methanol carbonylation in the presence of methyl iodide. , Inspired by reports from the Goldman group demonstrating net C–O bond activation via initial C–H bond activation, , and our own recent observation of ether decarbonylation via C–H bond activation, we turned to the dinitrogen complex [( MeO‑Et NCOP)­Ir] 2 (μ-N 2 ) ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although partial dissociation of the ligand was observed under catalytic conditions, stoichiometric studies established the viability of each reaction step, including Lewis acid promotion of the C–C bond-forming migratory insertion step . We recently isolated a NCOP iridium­(I)–dinitrogen compound and found that it facilitates decarbonylative C–O bond cleavage of ethers, initiated by C–H bond activation . These results led us to a stepwise study of iodide-free methanol carbonylation using methyl acetate as the methylating reagent.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation